Accuracy of four recent intraoral scanners with respect to two different ceramic surfaces. (March 2023) - Yatmaz, Berfin Bahar; Raith, Stefan; Reich, Sven
Abstract: Objectives: To investigate the complete arch accuracy of intraoral scanners (IOS) on two different ceramic surfaces. Methods: Two maxillary master cast samples were prepared. The bases of both the master casts were made from zirconium oxide. The difference between the two casts was that the teeth of the [ZR] cast were produced from zirconium oxide and that of the [LD] cast were made of lithium disilicate glass-ceramic. Unlike the zirconia teeth of the [ZR] cast, the lithium disilicate teeth of the [LD] cast were glazed. The two master casts were digitized using a high-resolution scanner (Atos Compact Scan 5 M, GOM GmbH, Braunschweig, Germany) to obtain digital reference casts. Subsequently, each master cast was scanned 15 times using four IOSs. The IOSs were the Cerec Omnicam [OM], Primescan [PR], Trios 4 [TR4], and VivaScan [VS]. On surface comparison, the absolute mean deviation values were obtained for trueness and precision. For multiple comparisons, statistically significant differences were analyzed using one-way ANOVA and the Kruskal-Wallis H test. The p-value was adjusted to control for the increased risk of type I error ( p < 0.0083). To compare the two means, the t- test and Mann-Whitney U test were used ( p < 0.05). Results: Trueness values for [ZR] ranged from 24.6 (±6.3) µm for [PR] and 77.1 (±8.3) µm for [OM]. Trueness values for [LD] were between 28.3 (±6.3) µm for [PR] and 72.8 (±15.6) µm for [OM]. Precision values for [ZR] ranged from 17.6 (±3.7) µm for [PR] to 37.3 (±9.9) µm for [OM]. Precision values for [LD] ranged from 17.5 (±3.6) µm for [PR] to 41.8 (±8.7) µm for [OM]. Statistically significant differences were found among all the IOSs ( p < 0.0083). The trueness values of the four IOSs did not differ significantly ( p < 0.05) with respect to either the [ZR] or [LD] cast. The precision values of [OM] and [VS] differed significantly with respect to the scanned surface. Conclusions: Complete arch scans achieved with the four IOSs showed significantly different trueness and precision results. [VS] and [OM] were more sensitive in terms of the scanned material. Clinical significance: The latest IOSs showed the required accuracy for complete arch digital impressions in-vitro investigations. These findings should be implemented under conditions relevant to complete arch deviations, such as the construction of occlusal splints, analysis of occlusal relationships, and long-span restorations. Clinicians should be aware that the clinically acceptable threshold varies depending on the purpose of the IOS.